Beta-catenin expression and allelic loss at APC in sporadic colorectal carcinogenesis. - Hao, X; Frayling, I; Willcocks, T; Han, W; Tomlinson, I; Pignatelli, M; Pretlow, T; Talbot, I (2002)
beta-catenin is involved in E-cadherin-mediated cell adhesion, intracellular signal transduction, and also interacts with adenomatous polyposis coli (APC) protein. We previously found that 31% of colorectal adenomas and 84% of carcinomas showed reduced membranous staining of beta-catenin, while 46% of adenomas and 79% of carcinomas displayed beta-catenin nuclear expression. Importantly, a reciprocal relationship between reduced membranous and increased nuclear beta-catenin expression was demonstrated in the development from adenoma to carcinoma. To clarify whether this relates to an abnormality of the APC gene ( APC), we have now studied allele loss in microdissected tissues from 74 adenomas and 21 carcinomas (sporadic cases, previously immunostained for beta-catenin) by analysis of the microsatellites D5S346, D5S82 and D5S299. Fifty-five tumors (57.8%) showed allele loss at APC (no difference between adenomas and carcinomas). Thirty-one of these 55 (31/55, 56.4%) displayed both increased nuclear localization and reduced membranous staining of beta-catenin, and thirteen tumors (13/55, 23.6%) manifested either nuclear expression without changes in membranous expression or reduced membranous staining without nuclear expression (9 and 4 cases, respectively), while 11 (11/55, 20.0%) preserved normal membranous expression. Adenomas and carcinomas showing both nuclear and reduced membranous expression of beta-catenin, compared with those with normal membranous expression, tended to show allele loss ( P<0.01). In addition, 24 (24/95, 25.6%) tumors showed a change in the pattern of beta-catenin expression, but did not exhibit allele loss. These results suggest that although there may be a number of mechanisms responsible for changes in beta-catenin expression in colorectal tumors, dysfunction of APC may be the major cause of this phenomenon.